First report of Macrophomina phaseolina causing leaf blight on Pometia pinnata in Malaysia - Khoo, Ying Wei; Khaw, Yam Sim; Tan, Hui Teng; Li, Shi-Fang; Chong, Khim Phin (Plant disease, 2023)
(family Sapindaceae), locally known as 'Kasai', is a tropical hardwood and fruit tree species grown in Malaysia. The decoction of the bark is used for the treatment of fever, sores and colds, while the fruits are edible (Adema et al. 1996). In May 2021, irregular brown spots and necrotic lesions were observed on 'Kasai' with an incidence and severity of approximately 60% and 10% on 10 plants in a nursery (5°55'30.7"N 116°04'36.2"E) in Penampang, Sabah province. When the disease progressed, the spots coalesced into extended patches, blightening the leaves and, gradually, the entire foliage. Small pieces (5 x 5 mm) of infected leaves were excised from the infected margin, and then surface sterilized according to Khoo et al. (2022b), and plated on potato dextrose agar (PDA), and cultured at 25 °C. for 6 days. Colonies were dark brown in color initially whitish on the PDA. The color of fungal colony was dark as the culture aged. Semi-appressed mycelia were observed on the plates with abundant microsclerotia engrossed in the agar. Aggregation of hyphae formed black and round to oblong or irregular shaped microsclerotia. Thirty sclerotia from a representative isolate measured average 63-171 μM length x 57-128 μM wide. The morphological features matched the description of (Abd Rahim et al. 2019). The fungal genomic DNA was extracted based on Khoo et al. (2022a and 2022b). PCR was performed using primer sets ITS1/ITS4 (White et al. 1990), EF1-728/EF2 (O'Donnell et al. 1998; Carbone and Kohn, 1999) and T1/T22 (O'Donnell and Cigelnik 1997) to amplify the internal transcribed spacer (ITS) region of rDNA, translation elongation factor 1-α ( ) region and partial β-tubulin ( ) gene. PCR products with positive amplicons were sent to Apical Scientific Sdn. Bhd. in Malaysia for sequencing. According to results (GenBank Accession No. OK465197, OM677767, ON237461), they were 100% identical with the reference sequence of Macrophomina phaseolina containing approximately 537 bp, 438 bp and 659 bp of the presented ITS, and (GenBank Accession No. MN629245, MN136199 and KF952208, respectively). The pathogen was identified as based on its morphological and molecular data (Abd Rahim et al. 2019). To confirm the pathogenicity test, three non-wounded and healthy leaves of one-month-old 'Kasai' seedlings were inoculated with mycelium plug (1 x 1 cm) of . Additional three 'Kasai' seedlings were inoculated with sterile PDA agar plug (1 x 1 cm) to serve as controls. The seedlings were monitored and incubated in a greenhouse at ambient temperature based on Iftikhar et al. (2022). After 6 days of inoculation, all infected leaves exhibited the symptoms as observed in the nursery, while the controls remained asymptomatic. The experiment was repeated twice. Re-isolation was performed from the symptomatic leaves and controls. The reisolated fungal isolates were identical to morphologically and molecularly. No pathogens were isolated from the mock controls. has been reported to cause leaf blight on in India (Mahadevakumar and Janardhana, 2016), and and in Malaysia (Abd Rahim et al. 2019). To our knowledge, this is the first report of causing leaf blight on 'Kasai' in Malaysia and worldwide. Our findings serve as a warning for the authorities and farmers that the disease threat has appeared for 'Kasai' in Malaysia.